Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5194/acp-21-11337-2021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Long-emission-wavelength chromophores dominate the light absorption of brown carbon in aerosols over Bangkok: impact from biomass burning

Abstract: Abstract. Chromophores represent an important portion of light-absorbing species, i.e., brown carbon. Yet knowledge of what and how chromophores contribute to aerosol light absorption is still sparse. To address this problem, we examined soluble independent chromophores in a set of year-round aerosol samples from Bangkok. The water-soluble fluorescent chromophores identified via excitation–emission matrix (EEM) spectroscopy and follow-up parallel factor analysis could be mainly assigned as humic-like substance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 101 publications
5
26
0
Order By: Relevance
“…Based on this simplistic bleaching model, the MAE 365 values of WSOC were 1.22 ± 0.86 and 1.32 ± 0.73 m 2 / gC for South and Southeast Asian source regions, respectively, which are within the range of those reported in pollution source regions in South, Southeast, and East Asia (Cheng et al, 2016;Geng et al, 2020;Kirillova et al, Kirillova Andersson,Tiwari et al, 2014Mo et al, 2021Tang et al, 2021;Yan et al, 2015).…”
Section: Light Absorption Properties Of Wsocsupporting
confidence: 61%
“…Based on this simplistic bleaching model, the MAE 365 values of WSOC were 1.22 ± 0.86 and 1.32 ± 0.73 m 2 / gC for South and Southeast Asian source regions, respectively, which are within the range of those reported in pollution source regions in South, Southeast, and East Asia (Cheng et al, 2016;Geng et al, 2020;Kirillova et al, Kirillova Andersson,Tiwari et al, 2014Mo et al, 2021Tang et al, 2021;Yan et al, 2015).…”
Section: Light Absorption Properties Of Wsocsupporting
confidence: 61%
“…The combination of excitation–emission matrix (EEM) spectroscopy and parallel factor analysis (PARAFAC) is broadly used in identifying the sources, structural information, and optical properties of chromophores in aquatic dissolved organic matter (DOM). Recently, EEM-PARAFAC has been extended and applied to investigations of atmospheric soluble brown carbon (BrC). However, the identification and chemical interpretation of PARAFAC-derived fluorescent components (FCs) is largely based on the knowledge of aquatic DOM. Studies have suggested that the sources and chemical composisiton of atmospheric organic matter (AOM) differ from those of aquatic DOM, ,, which may therefore lead to misinterpretations of the PARAFAC-derived FCs.…”
Section: Introductionmentioning
confidence: 99%
“…The higher content of C3 in WSOM in the dry season suggested the occurrence of more highly aromatic and highly oxidized compounds. These results could be explained by the fact that more aged organic aerosols and dust were transported from the northern region of China (Jiang et al, 2021). In contrast, the slightly higher C2 content in the wet season may be attributed to the relatively stronger secondary formation of bio-SOAs and photodegradation effects in high-temperature and relative humidity season.…”
Section: Spatial and Seasonal Variations Of Fluorescent Components In...mentioning
confidence: 97%